Comparing the neuropsychological profiles of mild dementia with Lewy bodies and mild Alzheimer's disease. Issue 1 (26th January 2018) - Xu, Yan; Chen, Keliang; Zhao, Qianhua; Guo, Qihao
Abstract : Background: The present study was conducted to detect neuropsychological differences and to identify discriminators between mild dementia with L ewy bodies (DLB ) and mild A lzheimer's disease (AD ). Methods: The present study included 37 mild DLB patients, 48 mild AD patients, and 80 healthy elderly individuals. A comprehensive battery of neuropsychological tests was administrated to assess their cognitive function. Linear stepwise discriminant analysis was used to identify the neuropsychological measures with values that could differentiate between mild DLB and mild AD . Results: The mild DLB group had greater impairments in attention, executive function, and visuospatial ability, while mild AD patients performed significantly worse on memory tests. Linear stepwise discriminant analysis indicated that the M emory and E xecutive S creening's 5‐min delayed recall test was the best neuropsychological discriminator between mild DLB and mild AD . Conclusions: Different patterns of cognitive impairment facilitate the differentiation of mild DLB from mild AD . For patients with mild dementia, better performance on the M emory and E xecutive S creening's 5‐min delayed recall test suggests that the diagnosis is more likely DLB than AD .